Essays on agribusiness capital management - Mashange, Gerald (Kansas State University, 2023)
Essay 1 Abstract: Valuing intangible capital in agribusinesses: A re-examination of the neoclassical theory of investment. The purpose of this paper is to examine the effect of intangible capital on investment rates in agribusiness firms. While tangible capital encompasses physical assets such as property and equipment, intangible capital includes items such as human capital, software, and brand value. The significance of intangible capital became evident in the 1990s with the rise of information technology and the growing disparity between firm market value and book value of physical capital. Investments in research and development can increase intangible capital stock, but this alone cannot account for all intangible investments and firm performance. This study leverages the neoclassical investment theory to understand how agribusinesses have capitalized on opportunities in the Digital Age through investment in employees, digital technologies, and data-driven growth. The results provide three key findings. First, total q is a better proxy for agribusiness investment opportunities than standard q whether cash flow is included in the investment equation or not. This means that intangible capital plays an important role in the neoclassical theory of investment for agribusiness firms. Second, the investment rates for agribusinesses facing financial constraints are more sensitive to cash flow than those not facing financial constraints. Lastly, agribusiness investment rates are explained more by total q and not cash flow. Essay 2 Abstract: Assessing the financial condition and accounts receivable risk among U.S. farmer cooperatives. The purpose of this paper is to examine the financial condition and ability of farmer cooperatives to withstand significant increases in bad debt expense. A unique data set of farmer cooperative financial statements that spans from 1996 to 2019 is used to examine the changes in profitability, solvency, liquidity, and accounts receivable risk. Also, a deterministic stress test model is designed to shock bad debt expense and the resulting write-off of accounts receivable for farmer cooperatives. The stress test provides insights to the resiliency of farmer cooperatives. Results find that farmer cooperatives are in a strong financial position, which has improved over time. The majority of farmer cooperatives are able to absorb a substantial increase in bad debt expense because of their sizable, retained earnings position. However, cooperatives that have significant profitability challenges do experience much larger losses, especially mixed farmer cooperatives (roughly equal amounts of grain and farm supply sales) and large cooperatives with more than $500 million in sales. The stress test results suggest farmer cooperative managers and boards of directors could re-examine their credit policies and consider extending additional credit. Also, cooperatives should consider monitoring and identifying an optimal accounts receivable to retained earnings ratio, which is similar to how banks examine their tier 1 capital ratios. The value of this study is having data that allows for the examination of the financial condition of farmer cooperatives over time. Also having current data means our accounts receivable stress test results are more relevant and timelier. This is important because these accounts receivable are primarily tied to crop input supplies and farmer cooperatives are a significant market participant in the crop input supply market. Essay 3 Abstract: Dynamic Pro-forma Tool for Kansas Farmer Cooperatives. This paper demonstrates how cooperative managers and directors can use the dynamic pro-forma tool to evaluate strategic decisions. The dynamic pro-forma financial tool is a three-statement financial model that allows users to input historical financial results and assumptions to project future financial performance. The U.S. farmer cooperative industry has undergone significant consolidation and experienced increasing complexity, leading to strategic challenges for cooperative managers and directors. Strategic planning sessions require the evaluation of proposals and their consequences on cooperative finances, with the current challenge lying in quantifying the impact of these proposals and visualizing their interdependencies. The dynamic pro-forma financial tool developed by the Arthur Capper Cooperative Center addresses these issues. Traditional pro-forma financial statements are limited in that the line items on the income statement and balance sheet change with the direction and relative size of revenues. The result is an inability to make specific projections for each line item. By more accurately presenting the forecasts of the income statement, balance sheet, and cash flow statement, the tool provides a comprehensive view of the impact of strategic decisions on a cooperative's projected financial health, including its liquidity and borrowing needs.
Keywords: Agribusiness; Capital; Stress testing; Farmer cooperatives; Pro-forma; Intangible capital